Lenguaje corporal y las relaciones interpersonales en los estudiantes de Comunicación Social de la Universidad Técnica de Babahoyo, Extensión Quevedo, año 2019 - Torres Marcillo, Yuli Isabel (2020)
This research project has its development from the problems evidenced in the UTB social communication career. Quevedo Extension, which is entitled Body language and interpersonal relationships in the students of social communication at the UTB. Quevedo Extension, year 2019, which is comprised of four chapters: Chapter I; The topic of the research project with which we will develop the work framed in their respective international, national, local and institutional contexts, in addition to the justification of the reason for the investigation, taking into account a very important factor, which consists of set objectives according to the subject, in addition to the respective variables. Chapter II; We will deploy the respective conceptual framework to investigate more deeply the subject, backed by authors who understand the subject and looking for the best research background, which will be very important to clear the hypotheses. Chapter III; In this chapter the project will be framed in the tools and methodologies that will be used for the correct collection of referential and statistical data, which with the correct interpretation and analysis will serve as a basis for decision-making aimed at solving the problem of the career of social communication. Chapter IV; The proposal will be developed to solve the problem posed in the previous chapters in terms of body language and body relations, providing them with the appropriate strategies, tools and guidance, with well-established objectives to achieve the expected results.